PEMANFAATAN TEKS BACAAN SATUA BALI DALAM MENUMBUHKAN BUDAYA LITERASI DAN PEMBENTUKAN KARAKTER PADA SISWA SEKOLAH DASAR - I KADEK MUSTIKA (Purwadita : Jurnal Agama dan Budaya, 2017)
The main problems encountered in education, especially in primary schools is the low interest in reading and the number of deviant behavior as a manifestation of bad character of students. In some of the results of research on reading interests, Indonesia ranks below countries in the world. So also with the problem of moral degradation, many behaviors such as violence, theft,  rape  and  others  that  reflect  not  maximal  character  education  among  children  and adolescents. To that end, efforts should be made pengintesifan increased interest in reading and character  education.  Satua  Bali  is  an  interesting  read  so  as  to  stimulate  students'  interest in reading and ultimately foster a culture of literacy. Satua also contains a lot of character values so it is suitable to be reading by elementary school students.